Interactive effects of protein and energy intake on nutrient partitioning and growth in Nile tilapia - G.D.P. Konnert; E. Martin; W.J.J. Gerrits; S.W.S. Gussekloo; K. Masagounder; J. Mas-Muñoz; J.W. Schrama (Animal, 2022)
Studies of fish growth response to changes in dietary protein and energy content are often conducted with fish fed to apparent satiation or at fixed percentages of their body mass. Such designs result in simultaneous changes in protein and non-protein energy intake, thereby failing to distinguish their separate effects on nutrient partitioning and growth. The present study was designed to address this limitation and test the existence of distinct protein- and non-protein energy-dependent growth phases in Nile tilapia (Oreochromis niloticus). All-male Nile tilapia (63 g, SD = 1.3) were subjected to an 8 × 2 factorial design consisting of eight levels of digestible protein (DP) intake (0.44–1.25 g/day) and two levels of non-protein digestible energy (NPDE) intake (16.0 and 22.4 kJ/day). Fish (n = 960) were housed in 60-litre tanks with two replicates per treatment and hand-fed twice a day for 42 days. Nutrient balances were calculated from changes in body mass, analysed body composition and digestible nutrient intake. Linear regression models were compared to linear-plateau regression models to determine whether protein gain followed distinct protein- and non-protein energy-dependent phases or not. Body mass gain increased linearly with increasing DP intake and was significantly higher (2.6 vs 2.3 g/d, P < 0.05) in fish receiving a high NPDE intake. This increase mainly reflected a higher mean fat gain (0.29 vs 0.20 g/d) rather than a higher protein gain (0.42 vs 0.39 g/d) in fish fed a high vs low level of NPDE intake. The comparison of linear and linear-plateau models did not give clear support for the presence of distinct protein and non-protein energy-dependent phases in protein gain. These results indicate that non-protein energy intake has a modest protein-sparing potential, and that protein gain is simultaneously limited by protein and energy intake in Nile tilapia.